Optimization of Ovarian Tissue Saturation with and Washing of Penetrating Cryoprotectants Solutions - Trutaeva, Irina A.; Kiroshka, Viktoria V.; Bozhkova, Yuliya O.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2015)
N/A